Blunt Ocular Trauma Complicated by Iridoplegia due to Suspected Traumatic Iritis: A Case Report - Pande Komang Wahyu Pradana; Ida Ayu Prama Yanthi (The International Journal of Medical Science and Health Research, 2025)
Background: Ocular trauma is defined as any injury affecting the eye and its surrounding structures. In Indonesia, ocular trauma is a leading cause of blindness, following cataracts, glaucoma, refractive errors, retinal disorders, and corneal abnormalities. Case: We report the case of a 52-year-old male patient who presented with a red eye after being struck by a wood splinter. Physical and ancillary examinations were conducted to establish a diagnosis of blunt ocular trauma complicated by iridoplegia secondary to suspected traumatic iritis. The patient received initial treatment in the Emergency Department, which included Prednisolone 10mg/ml administered six times daily to the left eye (OS) to reduce inflammation, Levofloxacin 5mg/ml administered six times daily as an antibiotic, and Diclofenac Sodium 50 mg taken orally twice daily. Conclusion: The primary goals of management for this patient were to restore vision and prevent infection. The purpose of this case report is to highlight the diagnostic and therapeutic approach in a patient with ocular trauma. Furthermore, the authors emphasize the critical role of ancillary examinations in this case.